Analysis of the Influence of Marketing Mix Toward Consumer Purchase intention at Burger Outlets in Manado, Airmadidi, and Bitung - Wahani, Vera; Walean, Ronny H. (8ISC Abstract Proceedings, 2022)
The fast-food culinary business is increasingly competing with the emergence of various fast food outlets. The marketing mix can be used to develop an effective marketing strategy for the business matter. The purpose of this study was to analyze consumer perceptions of the marketing mix, consumer perceptions of purchase intention, and the influence of seven elements of the marketing mix toward consumer purchase intention. This research was conducted using a descriptive method through a survey approach. The sampling technique was non-probability. This survey was conducted on respondents related to seven Burger outlets in Manado, Airmadidi, and Bitung. Multiple regression analyzes were used to analyze the data. The result showed that there is an influence of seven elements marketing mix towards purchase intention simultaneously. Partially, products, prices, physical evidence, and process were identified as significant variables influencing consumer purchase intention. And the physical evidence is the most significant variable. With the help of this research, Burger outlet owners can understand the influence of the marketing mix on customer purchase intention. Furthermore, the findings of this study will help Burger outlet owners to focus on improving the marketing mix elements that have a significant effect on customer purchase intention. Keywords : Marketing mix, purchase intention, burger